LA PROBLEMATIQUE DE MYOME UTERIN CHEZ LES FEMMES OPEREES DANS LES HOPITAUX GENERAUX DE REFERENCE DE KABONDO ET DE MAKISO A KISANGANI/RDC - IKEKE, Jérôme MOLIMA (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The utérine léiomyome is a more fréquent benign tumor at the woman in age to procreate. In 50% of case, the uterine fibromas are asymptomatiques and are not topics in any treatment. On 141 cases of uterine myoma constituting the women operated against 1115 patients registered for the surgical interventions, the prévalence observed in the two hospitals of reference of the City of Kisangani is of 12,6%. The most elevated rate is located on average in the age group of 38±4 years with 28,4%. Before the age of puberty, it has been objectified 0,7% of uterine myoma. The myomectomie constituted a record with 92,8%, the total hysterectomy and subtotale have been achieved representative respectively 5,5% and 1,1% of surgical treatmentit has been noted 9,2% of recidivism.